A Study on Employee Attrition at Firstsource Solutions Limited, Mumbai - Jain , Arjita (Gyan Management Journal, 2016)
This paper makes an attempt to find out the level of attrition at Firstsource Solutions Limited, Mumbai. Research type is descriptive. The study is based on both primary and secondary data. Primary sources comprise of interviews and responses collected through structured questionnaire. The primary data base has been framed from a sample of 70 employees. Data has been analyzed using excel. On the basis of research findings researcher has made certain suggestions to reduce the employee attrition at Fi rstso u rce ..
Keywords: Employee Attrition; Employee Retention; Compensation; Training & Development; Performance Appraisal